Implantable cardioverter defibrillator in nonischemic cardiomyopathy: A systematic review and meta‐analysis - Khan, Safi U.; Ghimire, Subash; Talluri, Swapna; Rahman, Hammad; Khan, Muhammad U.; Nasir, Fahad; Kaluski, Edo (Journal of arrhythmia, 2018)
The evidence to support implantable cardioverter defibrillator (ICD) in subjects with nonischemic cardiomyopathy (NICM) for primary prevention of sudden cardiac death (SCD) is not robust. This meta‐analysis intends to assess the impact of routine ICD implantation for primary prevention of mortality due to SCD in NICM based on all the published randomized clinical trials (RCTs). Six RCTs were selected using PubMed/Medline, EMBASE, and CENTRAL from inception to December 2016. Outcomes were calculated as random‐effects relative risk (RR) and risk difference (RD) with 95% confidence interval (CI). Patients were randomized to ICD arm and control arm (usual care, medical treatment, and anti‐arrhythmic drugs). ICD significantly reduced all‐cause mortality in NICM patients (RR, 0.74, 95% CI, 0.56‐0.97, P = .03, I2 = 40). Mortality benefit was achieved due to a significant reduction in sudden cardiac death (SCD) (RR, 0.47, 95% CI, 0.30‐0.73, P < .001, I2 = 0). There were no statistical differences between two groups with regard to risk of noncardiac mortality, non‐SCD, cardiac arrest, cardiac transplant, sustained ventricular tachycardia (VT), and VT requiring medical treatment. Our results support efficacy of ICDs at reducing all‐cause mortality due to a reduction in SCD.